Inhibitory Effect of Mexican Oregano (Lippia berlandieri Schauer) Essential Oil on Pseudomonas aeruginosa and Salmonella Thyphimurium Biofilm Formation - Reyes-Jurado, Fatima; Munguía-Pérez, Ricardo; Cid-Pérez, Teresa Soledad; Hernández-Carranza, Paola; Ochoa-Velasco, Carlos Enrique; Avila-Sosa, Raúl (Frontiers in Sustainable Food Systems, 2020)
Biofilms are difficult to eliminate with standard antimicrobial treatments due to their high antibiotic resistance. Therefore, some plants contain natural compounds with antimicrobial activity that can control biofilm formation. The aim of this work was to evaluate the effect of Mexican oregano (Lippia berlandieri Schauer) essential oil (EO) on Pseudomonas aeruginosa and Salmonella Thyphimurium biofilm formation on stainless steel surfaces. EO was added to achieve final concentrations of 0, 200, 250, 300, 400, 600, 800, and 1,600 mg/L. Growth data were modeled using the modified Gompertz model. EO antimicrobial activity against biofilm can be observed for both microorganisms. Moreover, at an EO concentration below inhibition, there is a delay in biofilm formation, thus decreasing the number of microorganisms that are part of the biofilm. The maximum growth rate in biofilm formation showed an inversely proportional behavior in relation to EO concentration. P. aeruginosa requires nearly 1 h to start forming biofilms. There is a delay in biofilm formation, thus decreasing the number of microorganisms that are part of the biofilm (24 h for 400 mg/L and 18 h for 600 mg/L). Salmonella Thyphimurium biofilm formation is affected at 200 mg/L of Mexican oregano EO, causing film detachment from the stainless steel surface after 18 h, while at 250 mg/L biofilm formation was inhibited. Mexican oregano EO could inhibit the development of P. aeruginosa and Salmonella Thyphimurium biofilm formation on stainless steel surfaces. Salmonella was more susceptible than Pseudomonas to Mexican oregano EO according to the concentrations required to inhibit biofilm growth.